Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan dengan Corporate Social Responsibility sebagai Variabel Moderasi - Razak, Linda Arisanty; Dewi, Putri Annisa; Nurhikmah, Nurhikmah; Ismi, Nur; Arham, Muh; Amirullah, Amirullah (Tangible Journal, 2023)
This study aims to determine the effect of financial performance on firm value with CorporateSocial Responsibility (CSR) as a moderating variable. This study uses a quantitative approach withsecondary data sources obtained from the official IDX website. The samples used in this study were23 companies in the Food and Beverage Subsector in the 2019-2021 period which were obtainedusing the Purposive Sampling method. The variables used in this study are Profitability (ROA),Liquidity (CR), Corporate Value (TobinQ) as a proxy, and Corporate Social Responsibility (CSR)as moderating variables. The data analysis technique in this study uses multiple linear techniques.The results of this study indicate that partially Profitability and Liquidity have no significant effecton firm value. Meanwhile, the analysis of moderating variables using the Moderated RegressionAnalysis (MRA) interaction test method shows that CSR disclosure can moderate ROA on firmvalue. While CSR cannot be able to moderate CR on Company Value.